The trouble with harry ebook - MacAlister, Katie (Noble, 2014)
Just what is the trouble with Harry? 1. He is Plum's new husband. Not normally a problem, but when you consider that Harry advertised for a wife, and Plum was set to marry his secretary, there was cause for a bit of confusion. 2. He has a title. Plum has spent the last twenty years hiding from the ton, and now Harry wants her to shine in society? 3. He doesn't know about her shocking secret. How is she going to explain about the dead husband who isn't a husband...and who now seems to be alive again? 4. He's fallen in love with her. And yet, the maddening man refuses to confide in her. Plum knows the real trouble with Harry is that he's stolen her heart. As a spy for the Crown, Lord Harry Rosse faced clever and dangerous adversaries—but it's his five offspring who seem likely to send him to Bedlam. At his wits' end, he's advertised for a wife and found one, but perhaps he should have been a bit more forthcoming on certain points... Frederica Pelham, affectionately known as Plum, spent years avoiding the scandals of her past, and is desperate for quiet security and a chance to make a family. What she finds is a titled husband and five little devils who seem bent on their own destruction, not to mention hers. And while all kinds of secrets are catching up with them, Plum knows the real trouble with Harry...